First stage larva of the mud shrimp Nihonotrypaea makarovi Marin, 2013 (Decapoda: Axiidea: Callianassidae) obtained in the laboratory - Korn, Olga M.; Kornienko, Elena S.; Golubinskaya, Darya D. (Zootaxa, 2016)
First stage larva of a new mud shrimp Nihonotrypaea makarovi Marin, 2013 (Decapoda: Axiidea: Callianassidae) obtained from the ovigerous female is described and illustrated for the first time. The first zoea of N. makarovi is well distinguished from the first larvae of N. japonica and N. petalura, sympatric callianassid species inhabiting Russian waters of the Sea of Japan, only by the greater size and by the presence of two terminal setae on the antennal endopod.